The Integration of ICT in the Classroom: Pre-Service EFL Teachers Experiences - Seli Marlina Radja Leba; I Gede Bagus Wisnu Bayu Temaja (Journal of Education Technology, 2023)
The use of ICT in teaching develops more important in present times because teachers also have to be able to keep up with the technological knowledge of their students. This study aims to analyze the pre-service teachers’ use of ICT in their classrooms during the practice teaching experience. This study employed both quantitative and qualitative data collection tools. The data were obtained from 86 pre-service teachers at senior high school and Junior High School. The data were collected qualitatively through observation and semi-structured interviews and quantitatively using a questionnaire. The qualitative results were mapped in tabular form. The researchers analyzed qualitatively to explain why pre-service teachers do not use ICT tools. The data were also made in tabular form and were described. The results showed that the practicum schools were not very rich in the technological devices offered to the pre-service teachers for their EFL classes. The pre-service teachers were not helped by ICT available to them in their teaching practice at a not satisfying level. Insufficient training, lack of basic facilities in the practicum schools, and pre-service teachers’ selections were the main reasons for teachers to utilize ICT in teaching practice. The study’s findings discovered a mismatch between teacher training programs and real-world classrooms in ICT integration in EFL instruction. Pedagogical inferences of the study consist of the need for better integration of ICT in EFL teacher training and a more vital link between the schools and the university.